Pengaruh Sarana Belajar dan Reward terhadap Minat Belajar Siswa Kelas Atas di SD Muhammadiyah 24 Surakarta Tahun Pelajaran 2015/2016 - Maryanto, Dedy Suryo Tri (2016)
Teaching-learning process/activity in high class of Muhammadiyah elementary school 24 of Surakarta, there is problems appeared for example students often make noisy or loud, do not pay attention material that is been learned and disturb their friends. This is indicating that learning interest of students is less. There is problem like this, teacher must cope it with various way such as optimize learning tool and give reward to the student. The objective of the study is to know the effect of learning tool and reward to learning interest both partially and simultantly. The type of the study done descpritive quantitative with ex-postfacto method. According to the result of the study gotten equation of doubled regression Y= 2.921 + 0,994X1 + 0.110X2. It indicates that regression coefficient of learning tool and reward have positive relation. From the equation, it is gotten prob.t of learning toll as 0,000. It means 0,000 > 0,05 and so that learning tool has effect to learning interest. And prob. t reward as 0,048. It means 0,499 > 0,05. So that reward has effect to learning interest. It is also gotten prob. F as 0000. Where 0,614 > 0,05. So that learning interest and reward simultantly have effect to learning interest.